Numerical Experiment Research on Failure Characteristics of Anchored Rock With Negative Poisson’s Ratio Bolt - Chen, Feng; Wang, Xue-Bin; Du, Yan-Hong; Tang, Chun-An (Frontiers in Earth Science, 2022)
With the continuous increase in the mining depth and engineering burying depth, the nonlinear physical and mechanical phenomena exhibited by rock are more complicated. The load value often exceeds the yield strength of the traditional Poisson’s ratio support materials, resulting in failure of the support body. Therefore, the bolt still needs further in-depth research into new materials. In this study, the numerical model with a negative Poisson’s ratio bolt had been established, the properties of negative Poisson’s ratio materials and the working principle of RFPA software were introduced, and RFPA software was used to study the reinforcement effect of negative Poisson’s ratio bolt on the rock. The numerical experiment results show that compared with the positive Poisson’s ratio bolt, the negative Poisson’s ratio bolt can significantly increase the bearing capacity of anchored rock; enhance the friction between the bolt, body, and the surrounding rock; and limit the rock movement. The anchored rock with a negative Poisson’s ratio bolt can absorb more energy. A negative Poisson’s ratio material is one of the future development directions of the bolt material.